A poesia como orientação em Arnaldo Antunes e Vilém Flusser - Maciel, Keila Mara de Souza Araújo (2012)
Searching new dialogues to enrich the analysis of Arnaldo Antunes visual poetry, this work promotes approaches to Vilém Flusser s philosophy, especially his concepts of language, technical images and communication. As we go deeper into the analysis of Arnaldo s work, the very "corporeality" of his poetic works place us face to face with the man-machine interface in the realm of cyber-art. In the construction of a theoretical argument, studies on casual conversation language and poetic language, contemporary aesthetics and electronic media are addressed; particularly the theories of Vilém Flusser, which take into account the interventions the electronic resources promote in human life and in the production of information and art.